Pengaruh Tanah Liat Terhadap Kreativitas Anak Usia Dini Di Taman Kanak-Kanak Aisyiyah 29 Tanjung Aur Padang - Intan Rahayu; Farida Mayar (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
This research originated from the fact that was found in Aisyiyah 29 Tanjung Aur Kindergarten, Padang, that children's creativity ability is not well developed, because the media is less varied. The aim of the researchers was to raise this title to find out whether clay influences the creativity of early childhood in Aisyiyah 29 Kindergarten Tanjung Aur Padang. Children's creativity can be developed through clay media. After going through the process and stages of clay can be used by children so that it is safe and harmless when forming activities with clay. The research method used is a quantitative method with experimental quasy types. Tests in the form of 4 items are used as data collection techniques, then processed using the t-test. The results of the post-test data analysis of the experimental class scored an average of 80 using clay activities and the control class gained an average of 71.67 using paper pulp.